The Effect of Audit Committee, Public Accounting Firm Reputation, and Investment Opportunity Set on Audit Report Lag - Fitriyah Fitriyah; Ovie Ayu Lestari (Transpublika Publisher, 2026)
The timeliness of financial reporting is a critical aspect of corporate transparency and investor decision-making, particularly in the banking sector where information asymmetry is pronounced. Delays in audit completion, commonly referred to as audit report lag, can undermine market confidence and regulatory compliance. This study aims to scrutinize the extent to which the audit committee, the reputational standing of public accounting firms (PAFs), and the investment opportunity set exert influence upon audit report lag in banking enterprises listed on the Indonesia Stock Exchange (IDX) spanning the period 2020-2024. A quantitative paradigm is employed, harnessing multiple regression analysis predicated on panel data through the Fixed Effects Model (FEM), encompassing 150 observations delineated via purposive sampling. The empirical findings divulge that the audit committee and the reputational standing of the PAF yield no discernible influence on audit report lag, whereas the investment opportunity set manifests a statistically significant bearing on the aforementioned variable. Concurrently, the audit committee, the reputation of the public accounting firm (KAP), and the investment opportunity set collectively exert a concomitant influence on audit report lag. These findings intimate that an augmentation in a company’s investment opportunities is consequential in prolonging the temporal span requisite for audit completion, whilst the presence of an audit committee and the reputational prestige of the KAP do not constitute determinative antecedents in the punctuality of audit reporting.